Building a knowledge map model situated in product design. (3rd December 2014) - Huang, Yongwen; Jiang, Zuhua; Liu, Lijun; Song, Bo; Han, Lijie
In product design, the complication of knowledge presentation and the scattered distribution of knowledge resources make knowledge sharing and reuse difficult. As an important knowledge management tool, knowledge map provides the knowledge sharing platform of knowledge assets. This paper proposes a knowledge map model and its building approaches. We present the knowledge map based on knowledge reuse process and its support to product design, also build a framework of knowledge map system. And then we analyse the key techniques: knowledge indexing, knowledge operation on the knowledge map, and the implementation of the knowledge map. By XML description method and scalable vector graphics (SVG) format map, concept knowledge map and process knowledge map can be used to reduce the islands of knowledge. These methods and technologies are verified in the automotive interior design process.